2004
DOI: 10.1152/ajpcell.00020.2004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for ERK1/2 phosphorylation controlling contact inhibition of proliferation in Madin-Darby canine kidney epithelial cells

Abstract: Increasing cell density arrests epithelial cell proliferation by a process termed contact inhibition. We investigated mechanisms of contact inhibition using a model of contact-inhibited epithelial cells. Hepatocyte growth factor (HGF) treatment of contact-inhibited Madin-Darby canine kidney (MDCK) cells stimulated cell proliferation and increased levels of phosphorylated ERK1/2 (phospho-ERK1/2) and cyclin D1. MEK inhibitors PD-98059 and U0126 inhibited these HGF-dependent changes, indicating the dependence on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…DNA laddering experiment showed that apoptosis was induced by serum starvation in both MDCK and b-KD cells indicating that reduced Na,K-b 1 expression does not protect cells from apoptosis. ERK1/2 phosphorylation has been shown to regulate contact inhibition of proliferation in MDCK cells grown in 2D culture (Li et al, 2004). Our results are consistent these findings in 2D culture.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…DNA laddering experiment showed that apoptosis was induced by serum starvation in both MDCK and b-KD cells indicating that reduced Na,K-b 1 expression does not protect cells from apoptosis. ERK1/2 phosphorylation has been shown to regulate contact inhibition of proliferation in MDCK cells grown in 2D culture (Li et al, 2004). Our results are consistent these findings in 2D culture.…”
Section: Discussionsupporting
confidence: 92%
“…S4), suggesting that knockdown of Na,K-b 1 did not protect the cells from apoptosis under serum starvation and that reduced apoptosis is likely to play a minimal role in lumen filling in b-KD cells. ERK1/2 activation is known to suppress contact inhibition of cell proliferation in MDCK cells and its phosphorylation levels decline as cells attain higher densities (Li et al, 2004). We hypothesized that increased ERK1/2 levels in b-KD cells are associated with enhanced cell proliferation and suppression of contact inhibition.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Activity of ERK has previously been linked to tubular cell proliferation (16), and ERK is upregulated in the Han:SPRD rat model of ADPKD (20). Furthermore, both ATP and UTP are potent activators of ERK in human intestine (38), and P2Y receptor-mediated activation of ERK via a cAMP-dependent pathway has also been shown to increase proliferation of dendritic cells (21).…”
Section: Discussionmentioning
confidence: 98%
“…C ells characteristically form epithelial monolayers through logarithmic growth when cells are subconfluent followed by cellto-cell contact and concluding with contact inhibition of proliferation (CIP), proliferative quiescence, and epithelial monolayer maturation, including tight junction (TJ) formation (1,2). CIP is an important step in monolayer maturation that is mediated in part by the activation of the Hippo pathway.…”
mentioning
confidence: 99%